Конструкции и детали из гипса в поточно-скоростном строительстве - Антипин А. А. (Книжное издательство, 1953)
Экземпляры: КХ (20120427) / Инвентарный номер: 166387 / Сис.шифр: 693.4 / Авт.знак: А 72 / ГРНТИ: 67 / ББК: 38